Diseño del sistema de conformado de fibra polimérica para reforzar concreto para Polyaltec LTDA. (2017)
The loads were established on the elements of the selected alternative, and the geometry of these elements was defined based on resistance calculations. From these calculations the structure and the rolls were validated in particles, this was done by the finite element method. The drawings of the elements of the machine, the safety, maintenance and operation manuals were elaborated. Finally, a study of manufacturing costs of the forming system was carried out; Obtaining satisfactorily an economic forming system, easy to manufacture and fulfilling the needs of the client.